2022
DOI: 10.1111/cpr.13313
|View full text |Cite
|
Sign up to set email alerts
|

Changes in OCT4 expression play a crucial role in the lineage specification and proliferation of preimplantation porcine blastocysts

Abstract: Objectives: Curiosity about the role of OCT4, a core transcription factor that maintains inner cell mass (ICM) formation during preimplantation embryogenesis and the pluripotent state in embryonic development, has long been an issue. OCT4 has a speciesspecific expression pattern in mammalian preimplantation embryogenesis and is known to play an essential role in ICM formation. However, there is a need to study new roles for OCT4-related pluripotency networks and second-cell fate decisions. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…The downregulation of the proapoptotic gene BAX and upregulation of the antiapoptotic gene BCL2 in the MA group also supported our hypothesis [ 42 ]. In addition, OCT4 plays a vital role in both cell fate decisions and cell proliferation in porcine early-stage embryos [ 43 ], while knockout of OCT4 inhibits blastocyst development [ 44 ]. Therefore, the OCT4 expression level is positively related to blastocyst pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of the proapoptotic gene BAX and upregulation of the antiapoptotic gene BCL2 in the MA group also supported our hypothesis [ 42 ]. In addition, OCT4 plays a vital role in both cell fate decisions and cell proliferation in porcine early-stage embryos [ 43 ], while knockout of OCT4 inhibits blastocyst development [ 44 ]. Therefore, the OCT4 expression level is positively related to blastocyst pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, Nanog works in concert with OCT4 . These genes are integral for maintaining embryonic stem cell pluripotency and promoting cell proliferation, and represent promising constituents for improving embryonic developmental quality (Hisey et al, 2021; Lee et al, 2022; Pan & Thomson, 2007) since IVC culture tends to accumulate excessive ROS levels that inhibit embryonic development (Kordowitzki, 2021; Wang, Tang, et al, 2021; Wang, Wu, et al, 2021). Therefore, after establishing NGR1 as effective in providing early development in porcine embryos, this study demonstrated that antioxidant NGR1 supplementation compensated for the IVC culture deficiency by increasing GSH and NRF2 levels while decreasing ROS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, OCT4 ‐GE blastocysts, although produced in vitro, did not show expansion or hatching after one additional day of culture until Day 7. Lee et al (2022) reported that OCT4 knockout in parthenogenetic porcine embryos decreased total cell number in blastocysts. Our results using fertilized oocytes are consistent in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In mice and pigs, OCT4 expression does not seem to be a prerequisite for blastulation (Lee et al, 2022; Nichols et al, 1998). On the other hand, to our knowledge, the importance of CD46 expression for in vitro development of porcine embryos has not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation